Resistance to ceftazidime–avibactam and underlying mechanisms - Yuhang Wang (Journal of Global Antimicrobial Resistance, 2020)
Objective: Ceftazidime–avibactam (CAZ-AVI) is a novel synthetic β-lactamase inhibitor combination. Although the combination has been available clinically for only a few years, cases of resistance to CAZ-AVI have already been reported. Methods: In the present review, we summarize the distribution of CAZ-AVI-resistant strains and the possible resistance mechanisms. Results: There are no significant differences in CAZ-AVI resistance rates across different regions. CAZ-AVI maintains good activity against Gram-negative bacteria, especially Enterobacteriaceae. Pseudomonas aeruginosa is less susceptible to CAZ-AVI compared with Enterobacteriaceae, with a resistance rate ranging from 2.9 to 18%. The resistance to CAZ-AVI exceeds 50% in Acinetobacter baumannii. A higher resistance rate to CAZ-AVI is associated with carbapenem resistance. Moreover, β-lactamase-related amino acid substitutions are the main mechanisms that lead to CAZ-AVI resistance. Membrane protein amino acid substitutions and efflux pumps also play important roles in CAZ-AVI resistance. Conclusions: To maintain its efficacy, CAZ-AVI should not be used for pathogens that are naturally resistant to it. For CAZ-AVI-resistant strains, other effective antibacterial agents or CAZ-AVI in combination with other antibacterial agents should be considered.